Haemophagocytic lymphohistiocytosis secondary to brucellosis in a young child. Issue 3 (10th March 2021) - Mittal, Jashan; Kumar, Prawin; Goyal, Jagdish Prasad; Purohit, Abhishek
Abstract : Brucellosis is a common zoonotic disease worldwide. It has protean clinical manifestation and sometimes may has a life-threatening complication. A 4-year-old boy presented with a history of fever, myalgia and appetite loss for 3 weeks. On examination, he had hepatosplenomegaly. The initial working diagnosis was an infection, autoimmune disease and malignancy. Investigations showed positive Brucella serology, and he was started on rifampicin and cotrimoxazole. He was further investigated because of persistent fever, which revealed evidence of haemophagocytic lymphohistiocytosis (HLH). He continued treatment for brucellosis, except rifampicin which was replaced with doxycyclin due to a worsening liver function. The child showed complete clinical and biochemical improvement after 6 weeks of therapy. HLH is a life-threatening condition and should be suspected in children with brucellosis, who did not respond to appropriate antibiotics treatment. Secondary HLH does not always require specific therapy; it may improve with adequate treatment of the underlying condition.